The Effect of Education on Writing Integrated Patient Progress Notes (IPPNs) at Several Government Hospitals in Bukittinggi, Indonesia - Serdiani Suhaili; Hansen Nasif; Yelly Oktavia Sari (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: The writing of Integrated Patient Progress Notes (IPPNs) by pharmacists generally does not fulfil the correct writing standards. Objective: This study aimed to analyze the effect of education on the level of knowledge and writing profile of IPPN. Methods: A prospective analytic method research design was used with data collection techniques through questionnaires and total sampling for IPPN data. The researcher developed a valid and reliable questionnaire to measure pharmacists' level of knowledge. Education was conducted through "Focus Group Discussion" with PowerPoint slides of SOAP method writing material and SOAP framework leaflets. Quantitative analysis of IPPN data was performed using the Wilcoxon test on SPSS. Results: The results showed that the highest percentage of pharmacists' knowledge level before education was A.M Hospital (87%) and after education was B Hospital (95%). The profile of IPPN writing by pharmacists before being given education showed the highest percentage of IPPN writing suitability was at A.M Hospital (21.6%), and the completeness of IPPN writing was at M.H Hospital (99%). After education, the highest percentage of IPPNs writing suitability was in B Hospital (64.3%), and the completeness of IPPNs writing was in M.H Hospital (97.9%). Education has an effect on pharmacists' knowledge level (p-value 0.029) and the appropriateness profile of IPPN writing (p-value 0.013). However, education did not affect the completeness of writing Integrated Patient Progress Notes (IPPNs) (p-value 0.285). Conclusion: Education succeeded in improving pharmacists' knowledge of writing CPPT correctly.